2004
DOI: 10.1021/ja0472073
|View full text |Cite
|
Sign up to set email alerts
|

A Transition State Analogue for an RNA-Editing Reaction

Abstract: Deamination at C6 of adenosine in RNA catalyzed by the ADAR enzymes generates inosine at the corresponding position. Because inosine is decoded as guanosine during translation, this modification can lead to codon changes in messenger RNA. Hydration of 8-azanebularine across the C6-N1 double bond generates an excellent mimic of the transition state proposed for the hydrolytic deamination reaction catalyzed by ADARs. Here, we report the synthesis of a phosphoramidite of 8-azanebularine and its use in the prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 48 publications
1
84
0
Order By: Relevance
“…In support of this mechanism, we have shown that 8‐azanebularine (8‐azapurine ribonucleoside), when incorporated at a known editing site in a model RNA substrate, binds tightly to ADAR2 and the deletion mutant lacking dsRBM I 54. This binding requires a functional active site, consistent with the hypothesis that the high‐affinity binding occurs to the covalent hydrate, which is an excellent mimic of the proposed reaction transition state (Scheme ).…”
Section: Adars: Rna Editing and The Nervous Systemsupporting
confidence: 68%
“…In support of this mechanism, we have shown that 8‐azanebularine (8‐azapurine ribonucleoside), when incorporated at a known editing site in a model RNA substrate, binds tightly to ADAR2 and the deletion mutant lacking dsRBM I 54. This binding requires a functional active site, consistent with the hypothesis that the high‐affinity binding occurs to the covalent hydrate, which is an excellent mimic of the proposed reaction transition state (Scheme ).…”
Section: Adars: Rna Editing and The Nervous Systemsupporting
confidence: 68%
“…The combination of binding from dsRBDs and the deaminase domain must provide enough binding energy to allow the base flipping loop to intercalate residue E488, stabilize the distortion surrounding the flipped base and overcome the stress induced by the close approach of G489 to the 5′ nearest neighbor base pair. Indeed, biochemical studies with models of the GluR B R/G site support this idea . Although these RNAs are poor substrates for ADAR2's deaminase domain because they lack the region 3 contact surface, they react efficiently with a protein composed of the ADAR2 deaminase domain and dsRBD2 (see below in the Section dsRBD binding is required for editing of some substrates).…”
Section: Adar Substrates May Lack Contacts Observed In the Crystal Stmentioning
confidence: 99%
“…ADAR is essential in all animals examined to date, and studies in mouse, Caenorhabditis elegans, and Drosophila suggest that the function of pre-mRNA editing is to modify adult behavior by altering signaling components in the nervous system (Higuchi et al 2000;Palladino et al 2000;Wang et al 2000;Tonkin et al 2002). Considerable progress has also been made in understanding the mechanism of action of the ADAR enzyme (Cho et al 2003;Haudenschild et al 2004;Athanasiadis et al 2005;Macbeth et al 2005). The molecular details of target site specificity of RNA editing are drawn from studies of the mammalian glutamate receptor gene, GluR-B.…”
Section: Introductionmentioning
confidence: 99%